Lipoma of the fossa femoralis mimicking a femoral hernia. Report of 2 cases. (2018) - Amato, G.; Romano, G.; Agrusa, A.; Rodolico, V.; Gordini, L.; Calò, P.G.
Highlights: Femoral lipoma can be mistaken with femoral hernia. Differential diagnosis between femoral lipoma and femoral hernia can result challenging. The occurrence of femoral pain can lead to misinterpretation of the symptoms. Abstract: Introduction: Lipoma of the femoral fossa is uncommon. Often asymptomatic, femoral lipoma may growth within the circumscribed space of the femoral fossa causing pain and discomfort. A worsening pain caused by a lipomatous mass in the femoral area is a clinical feature that can mislead the diagnosis, resembling the more common condition of femoral hernia. Methods: Two cases of symptomatic lipomas of the femoral fossa mimicking an incarcerated femoral hernia are presented. In both, Caucasian female, patients clinical examination and ultrasound of the femoral region revealed a painful neoplasm suspected for incarcerated femoral hernia. Results: Intraoperatively, a mass of encapsulated fat arising from the bottom of the fossa femoralis was found. No visceral protrusion through the femoral ring could be documented. The neoplasms were removed in toto. Histology of the excised specimens evidenced the diagnosis of femoral lipomas suffering by chronic compressive damages. In a midterm postoperative follow up, both patients were symptom- free. Discusion: A correct preoperative diagnosis of femoral lipoma is challenging, even following an accurate diagnostic pathway. The cases highlighted herewith seem to confirm that lipoma of the femoral fossa can be mistaken with a femoral hernia. Conclusions: The clinical and histological features evidenced could result helpful in the differentiation of a lipomatous mass of the femoral fossa from a genuine femoral hernia.